Physical activity and eating habits of students of the University of Belgrade: An epidemiological study - Obradović Miloš; Nešić Goran; Popović Aleksandra; Božić Predrag; Savić Zoran; Kojić Filip; Đurić Saša (Vojnosanitetski Pregled)
Background/Aim. Numerous studies have indicated that university students exhibit a variety of risky health behaviors, such as the lack of regular physical activity and u n-healthy eating habits. Due to lack of information about students’ lifestyles in Serbia, we designed a study with the following aims: 1) to investigate physical activity and eating habits variations of students according to gender, year of study and attended faculty; 2) to estimate the relationship between their physical activity and eating habits. Methods. The survey method was used. Data were collected in the 2016/2017 school year during the spring semester. The sample was randomly stratified (4,019 students of the University of Belgrade – 2,284 males), which corresponded to about 5% of the whole student population of the University of Belgrade. For data collection, two standardized questionnaires were used: International Physical Activity Questionnaire (IPAQ) and Youth/Adolescent Food Questionnaire (YAQ). Results. Male students were significantly more highly and moderately active than female students [3.15 vs. 2.80 days, respectively; p = 0.003, effect size (ES) = 0.651]. Correspondingly, female students were less active during the day (326 vs. 305 min; p = 0.044, ES = 0.232). Interaction between factors revealed that the most active on a weakly basis were fourth-year male students of the natural sciences (4.20 days), while on a daily basis, the most active were first-year female students (161 min). The most sedentary ones were third-year female students of medical sciences (475 min of sitting per day). Significant correlations were found between the duration of intense physical activity and consuming water, vegetables, citrus fruits, integral bread, and cereals. Conclusion. Female students were more prone to sedentary behavior, while older students were more active and aware of the importance of physical activity. Further-more, the nature of studies can influence the lifestyle. Female and older students were more concerned about diets. Additionally, students who were more physically active had healthier eating habits.